Biomarkers and Cellular Biology in Perioperative Medicine - Jan Larmann; Markus M. Luedi (Cells, 2022)
Surgical procedures alter tissue integrity; are associated with pain and activation of the sympathetic nervous system; and sometimes, cause exposure to foreign materials used during the surgery or implanted perioperatively [...]